Icaritin-Induced FAM99A Affects GLUT1-Mediated Glycolysis via Regulating the JAK2/STAT3 Pathway in Hepatocellular Carcinoma - Xia Zheng; Xia Zheng; Yudong Gou; Ziyu Jiang; Ziyu Jiang; Aizhen Yang; Zhihui Yang; Shukui Qin; Shukui Qin (Frontiers in Oncology, 2021)
Icaritin is a potential treatment option for hepatocellular carcinoma (HCC) based on the results of its phase 2 stage trial. Glucose transporter 1 (GLUT1), a critical gene in regulating glycolysis, has been recognized as a promising target in HCC treatment. Previous studies have reported that FAM99A, a new long noncoding (lncRNA), is associated with HCC metastasis. It has also been demonstrated that the JAK2/STAT3 pathway is related to HCC and is the target of icaritin treatment. However, whether FAM99A participates in icaritin treatment and regulates GLUT1-mediated glycolysis via the JAK2/STAT3 pathway in HCC cells remains to be explored. Our study aimed to clarify the mechanisms underlying glycolysis and understand the regulating effects of the FAM99A and JAK2/STAT3 pathway in HCC cells in icaritin treatment. Molecular mechanism studies were conducted to verify whether FAM99A could bind to the JAK2/STAT3 pathway and to identify the regulatory mechanisms in the HCC cells. It was revealed that icaritin inhibited proliferation, GLUT1 level, and the glycolysis of the HCC cells. FAM99A in HCC cells was upregulated after a high concentration treatment of icaritin. FAM99A inhibited GLUT1 by blocking the JAK2/STAT3 pathway. Mechanically, FAM99A interacted with EIF4B to inhibit gp130 and gp80 translation, which then interacted with miR-299-5p to upregulate SOCS3, causing the JAK2 pathway to inhibit STAT3 phosphorylation, so that JAK2/STAT3 was blocked in HCC cells. Overall, our study proved that icaritin-induced FAM99A can inhibit HCC cell viability and GLUT1-mediated glycolysis via blocking the JAK2/STAT3 pathway.